If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(7y + 7) = 0 Reorder the terms: -5(7 + 7y) = 0 (7 * -5 + 7y * -5) = 0 (-35 + -35y) = 0 Solving -35 + -35y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + -35y = 0 + 35 Combine like terms: -35 + 35 = 0 0 + -35y = 0 + 35 -35y = 0 + 35 Combine like terms: 0 + 35 = 35 -35y = 35 Divide each side by '-35'. y = -1 Simplifying y = -1
| 2/3x-6=-24 | | x^2-180+12x-6=0 | | 18(m+0.44)-16=18 | | 9r^2+14r+40=0 | | 2/5x-1/2x=x-3/4 | | 6(2v+7)(v+6)/24(v-5)(2v+7) | | 4x-5-2x=4 | | (X/5)-(x/3)=2 | | 2x^3-5x^2+7x-23=0 | | 6/8=x+1/4 | | 36-4x=28 | | 12(n+1)-11n+2(n+1)=56 | | 9x-7xy-6= | | x^4+2x^3+2x^2-3x-2=0 | | R=2pirh | | 0+a=a | | 7x+65/89 | | 20-5x-8xy= | | x^2+2x=16384 | | y=x^2+3x+18 | | t^2-162=0 | | 9p=6p | | x^2+3x=2187 | | y=-.4x | | -8p=-3/4 | | 2x+1=6x+9 | | 1.4x=12 | | t=-5x+3y | | 5=3y+2x | | 0.07t=0.77 | | 42-2x=36 | | h-48=17h+42 |